2005
DOI: 10.1055/s-2005-873077
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of the Sensorimotor Cortex - A Developmental fMRI Study

Abstract: Children show a significant difference in the degree of cortical activation compared to adults when performing a simple motor task. The change in fMRI activation patterns may reflect a maturation process of primary and secondary motor areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
4
14
0
1
Order By: Relevance
“…Regardless of cognitive or motor-related circuits, most frontal-striatal networks showed a similar inverted ''U'' pattern among three age groups, suggesting similar development and aging processes across the two types of circuits. Multiple developmental studies have documented that children can have adult-like performance in a wide range of motor tasks (e.g., Mall et al, 2005;Thomas et al, 2004). For example, Mall and coworkers (2005) have reported that children as young as 6 years of age could perform simple-paced unilateral motor tasks (e.g., squeezing a ball) at the mature adult level.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of cognitive or motor-related circuits, most frontal-striatal networks showed a similar inverted ''U'' pattern among three age groups, suggesting similar development and aging processes across the two types of circuits. Multiple developmental studies have documented that children can have adult-like performance in a wide range of motor tasks (e.g., Mall et al, 2005;Thomas et al, 2004). For example, Mall and coworkers (2005) have reported that children as young as 6 years of age could perform simple-paced unilateral motor tasks (e.g., squeezing a ball) at the mature adult level.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these studies have shown no clear consensus regarding the maturational trajectory of these networks. In one study, children who performed a simple motor task showed an increased amount of activation outside the primary motor cortex compared to adults who performed the same task (Halder et al, 2007;Muller et al, 1998) while in two others children showed a relative decrease in the amount of activation (Guzzetta et al, 2007;Mall et al, 2005). The discrepancy between the studies may result from methodological differences including the task chosen and the age-range of the subjects.…”
Section: Relationship Between Tms-evoked Parameters and Neuromotor Fumentioning
confidence: 99%
“…Some knowledge about active motor tasks derives from studies with small control groups (3,10), which showed similar patterns of activation to those reported in adult studies (5,9,11,12). Nevertheless, the only study that systematically compared active movements in children and adults (repetitive hand squeezing of a ball) reported a significantly wider activation in the latter, particularly at the level of the primary SMC, the SMA, and the cerebellum (13). No studies on passive movement in normal children have been published so far, and no data are therefore available comparing children and adult passive movements or active and passive tasks in children.…”
mentioning
confidence: 95%